2014
DOI: 10.1371/journal.pone.0104364
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Integrity Is Required for the Maintenance of Long-Term Synaptic Plasticity

Abstract: Long-term memory (LTM) formation requires new protein synthesis and new gene expression. Based on our work in Aplysia, we hypothesized that the rRNA genes, stimulation-dependent targets of the enzyme Poly(ADP-ribose) polymerase-1 (PARP-1), are primary effectors of the activity-dependent changes in synaptic function that maintain synaptic plasticity and memory. Using electrophysiology, immunohistochemistry, pharmacology and molecular biology techniques, we show here, for the first time, that the maintenance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 56 publications
(74 reference statements)
1
34
0
Order By: Relevance
“…It has to be noticed that similar conclusions have also been reached through in vitro experiments (Allen et al . ). Interestingly, previous studies demonstrated that mRNAs coding for ribosomal proteins are present at synapses (Moccia et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has to be noticed that similar conclusions have also been reached through in vitro experiments (Allen et al . ). Interestingly, previous studies demonstrated that mRNAs coding for ribosomal proteins are present at synapses (Moccia et al .…”
Section: Discussionmentioning
confidence: 97%
“…This observation is in line with a recent study (Allen et al . ) demonstrating that the blockade of rRNA transcription in vitro impairs the long‐term potentiation of hippocampal synapses, a process known to share several molecular commonalities with memory formation (Morris et al . ; Giese et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, induction of long term potentiation (LTP) or spatial learning is associated with increased Pol1 activity [22,23]. In addition, LTP is disrupted by genetic or pharmacological inhibition of hippocampal Pol1, while the latter manipulation also negatively effects spatial memory consolidation [24,23,22]. Importantly, these defects are unlikely to be due to neuronal death, as mature forebrain neurons survive for months without active Pol1 [25,24].…”
Section: Introductionmentioning
confidence: 99%
“…The observation reported here of an increased rRNA transcription upon learning and the need of nucleolar integrity for the maintenance of LTM and LTP confirms nicely the earlier in vitro observations made in mouse hippocampal slices (Allen et al . ). However, methods used by Capitano and co‐workers (JNC, this issue) raise several additional questions, to be urgently addressed in order to elucidate the complex intra‐ and interneuronal molecular processes, associated with learning.…”
mentioning
confidence: 97%